The journalistic logic in epistemological sense - Parra Pujante, Antonio (Estudios sobre el Mensaje Periodístico, 2012)
This article supposes a sketch of philosophy of the journalistic information and, in last instance, an advance of Theory of the Truth applied to the informative practice, as it is given, in a royal way, consciously or not, in the activity of the professional journalists. The media information, which might affiliate to a root of the Jewish truth in the sense in which he needs from the confidence (emunah) from the user, gets stuck in the adecuatio; also, certainly, in Popper’s fallibilism, and, beyond the isomorphism of Wittgenstein in the Tractatus, his terms of reference connote and presuppose real reality, not only to the “unspeakable thing”, but even to the lie. Only the normative, ethical moment, there corrects this dream of the journalistic and false logic his claimed absolute objectivity of procedural character.